Experiments on electromagnetic interaction of linearly polarized photons with nucleons and nuclei - Gorbenko, V.G.; Kolesnikov, L.Ya. (Вопросы атомной науки и техники, 2003)
Experiments on electromagnetic interaction of nucleons and nuclei with linearly polarized photon beams produced by coherent bremsstrahlung of high energy electrons from diamond single crystal targets are reviewed. The details of experimental equipment, the methods of beam monitoring and photon polarization evaluation, as well as the methods for measuring cross section asymmetries are discussed. The experimental results for polarization parameters of pion photoproduction and photodisintegration reactions are presented and discussed along with theoretical analyses. Розглянуто експерименти з електромагнітної взаємодії нуклонів та ядер з лінійно поляризованими фотонними пучками, які отримані в результаті когерентного випромінювання електронів з високими енергіями на мішені з кристалу алмаза. Дискутуються деталі експериментального обладнання, методи моніторування пучка та визначення величини поляризації фотонів, а також методи вимірювання асиметрії перерізів. Експериментальні результати для поляризаційних параметрів фото народження піонів та реакцій фото дезінтеграції, що представлені, дискутуються наразі з теоретичним аналізом. Рассмотрены эксперименты по электромагнитному взаимодействию нуклонов и ядер с линейно поляризованными фотонными пучками, производимыми в результате когерентного тормозного излучения электронов с высокими энергиями на мишени из кристалла алмаза. Обсуждаются детали экспериментального оборудования, методы мониторирования пучка и определения величины поляризации фотонов, а также методы измерения асимметрии сечений. Представленные экспериментальные результаты для поляризационных параметров фоторождения пионов и реакций фотодезинтеграции обсуждаются наряду с теоретическим анализом.